The effectiveness of technological resources applied as didactic tools in the english language learning process to students of 9th level at the Beatriz Miranda de Cabal High School located in Dolega, Chiriquí - Acosta M., Beatriz (UDELAS, 2011)
Far many years, people around the world have tried to use technology as a teaching resources for the teaching of the english language. Furthemore, this issue has become very important in the educational field as it came to make changes to traditional ways of teaching and learning with the purpose to increase and improve the effectiveness of teachers' tasks at the same time students' uderstanding.